Gender characteristics associated to acute respiratory failure in pre-hospital emergency medical services A observational study - Cintora-Sanz, Ana María; Gutiérrez-Misis, Alicia (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
Background: The descriptive casuistry of acute respiratory failure in out-of-hospital emergencies is unknown. Objectives: To assess the gender of acute respiratory failure, both isolated and related to chronic respiratory failure, as well as acute pulmonary edema (PAD). Main results: Of the 40,130 patients, 54.45% were women versus 45.54% men in the EAP. In acute respiratory failure not related to chronic respiratory failure, the percentage of women was 56.53% and that of men 43.47%. In acute respiratory failure related to chronic respiratory failure, the male sex was 55.6% and the female 44.4%.